PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS BANK DI BURSA EFEK INDONESIA - Nathalie, Divina Grace Yuliantika; Fadjar, Nurman Setiawan (Contemporary Studies in Economic, Finance and Banking, 2023)
Working capital management in banking is important for the management of liquid assets. The development of digitization requires banks to provide larger capital for company development while still being able to generate profits for the bank. This research aims to identify the influence of working capital management on bank profitability. The research model uses panel data with research objects consisting of 36 conventional commercial banks listed on the Indonesia Stock Exchange from 2017 to 2021. Partially, this research found a significant positive relationship between Quick Ratio, Investing Policy Ratio, Loan to Deposit Ratio, Debtors Collection Period, Creditors Payment Period, and Loan Losses Provision to Return On Assets. This research also shows a significant impact of working capital management on bank profitability.